Development of Manipulative Number Card Media in Mathematics Learning at Madrasah Ibtidaiyah Muhammadiyah Trangsang Sukoharjo - Chasanah, Salma Alvie; Al Farisi, Salman; Praptiningsih, Praptiningsih (FONDATIA, 2025)
This study is motivated by the limited research on the development of manipulative number card media in elementary mathematics education, despite its strong potential to enhance students’ conceptual understanding. The research aims to analyze the effectiveness of manipulative number card media in improving third-grade students’ comprehension of simple fractions and to describe the process of its development. Utilizing a Research and Development (R&D) approach based on the ADDIE model, the study involved 64 third-grade students at MI Muhammadiyah Trangsan Sukoharjo, selected through purposive sampling. Data were gathered through observations, interviews, questionnaires, and achievement tests, and analyzed using quantitative descriptive methods. The results demonstrate high feasibility ratings for the developed media, with scores of 97% from media experts, 100% from material experts, 93.75% from teachers, and 96.81% from students. The average post-test score was 95.04, indicating excellent student performance. These outcomes support the learning theories of Piaget and Bruner, emphasizing the critical role of concrete manipulative media in facilitating students’ understanding of abstract mathematical concepts. The study concludes that manipulative number card media is an effective tool for mathematics instruction and highlights the potential for future research to expand its application to other mathematical topics. Keywords: Manipulative Media; Number Cards; Mathematics Learning; Elementary Education; Media Development